The Visual Representation of Seniors on Social Media: Spanish Banking Brands and Their Response to the Silver Economy - Martín Martín, Irene (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
Population aging has sparked increasing interest from banking brands to engage the senior segment, a key player in the so-called «Silver Economy». This study examines the representation of seniors in the social media communication strategies of major Spanish banking entities, assessing whether ageist stereotypes have been overcome. Through qualitative content analysis, the study reviewed posts from selected brands based on their relevance in the Corporate Reputation Business Monitor (MERCO). Results reveal recurring patterns in the use of visual and narrative elements that reinforce values associated with active aging. However, barriers persist in the digital inclusion of more vulnerable seniors. This article provides new approaches for adapting advertising strategies within a framework of more inclusive and humanized communication.